2022
DOI: 10.3389/fimmu.2022.917739
|View full text |Cite
|
Sign up to set email alerts
|

A Fenton-like cation can improve arsenic trioxide treatment of sclerodermatous chronic Graft-versus-Host Disease in mice

Abstract: Graft-versus Host Disease (GvHD) is a major complication of hematopoietic stem cell transplant. GvHD is characterized by the chronic activation of immune cells leading to the development of systemic inflammation, autoimmunity, fibrosis and eventually death. Arsenic trioxide (ATO) is a therapeutic agent under clinical trial for the treatment of patients with systemic lupus erythematosus (SLE) and chronic GvHD (cGvHD). This therapy is admittedly rather safe although adverse effects can occur and may necessitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…With regard to the results obtained in a previous work published in Frontiers in Immunology ( 14 ), we chose the lowest copper concentration that modified the GSH concentration and the survival rate in tumor cells. This choice was also determined by the fact that we wanted to use the lowest dose to avoid toxicity in animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the results obtained in a previous work published in Frontiers in Immunology ( 14 ), we chose the lowest copper concentration that modified the GSH concentration and the survival rate in tumor cells. This choice was also determined by the fact that we wanted to use the lowest dose to avoid toxicity in animals.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those of previous studies by Kavian et al., who showed that ATO decreased skin fibrosis in a mouse model of chronic cGvHD and in the mouse model of SSc ( 7 , 24 ). Furthermore, we recently demonstrated that CuCl 2 potentiates the therapeutic effect of low-dose ATO alone on skin fibrosis in a mouse model of sclerodermatous cGvHD ( 14 ). In humans, an effective dose (0.16 mg/kg) can induce side effects such as skin reactions, gastrointestinal disorders and a reversible increase in transaminases, leading to discontinuation of treatment ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 50 million people from West Bengal and Bangladesh were exposed to arsenic levels above 50 μg/L, which caused frequent arsenic poisoning and adverse effects on human health . A growing body of literature suggests that arsenic disrupts a series of cellular processes, including oxidative stress, cell proliferation, inflammation, and autophagy and apoptosis. , Arsenic exposure can lead to many adverse health effects of diabetes mellitus (DM), skin lesions, , kidney disease, , neurological impairment, , cancers, , male reproductive injury, and cardiovascular disease (CVD) as cardiac arrhythmias, endothelial dysfunction, and ischemic heart failure. , …”
Section: Introductionmentioning
confidence: 99%